Media Sosial sebagai Pengganti Institusi Tradisional dalam Pembentukan Norma Sosial - Amaani, Fauziyyah; Al-Ghifary, Muhammad Firdhi; Amelia, Nanda; Azizah, Sarah Nur; Hufad, Achmad; Achdiani, Yani (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2025)
Social media has transformed the social dynamics of modern society, replacing the role of traditional institutions in shaping social norms. Institutions such as family, school, and religionÃ¢â‚¬â€previously the main pillars in constructing social valuesÃ¢â‚¬â€are now being displaced by the influence of digital media. This study aims to analyze how social media functions as a new institution in the formation of social norms, using the perspective of Talcott Parsons' Structural Functionalism Theory, particularly the AGIL framework (Adaptation, Goal Attainment, Integration, and Latency). A qualitative method was employed, involving teenage participants aged 17Ã¢â‚¬â€œ20 who are actively engaged with social media. The findings show that social media not only facilitates communication but also establishes new standards in social behavior, moral values, and political engagement. Therefore, social media has emerged as a new institution that defines social norms, replacing the role of traditional institutions in society.